TRACING GENDER PERSPECTIVES IN LITERATURE: THE SEARCH FOR ISLAMIC FEMINISM IN FAITH AND THE CITY BY HANUM RAIS (International Conference on Social and Islamic Studies, 2022)
This is the study with a concern to reinterpret the feminist ideas on an autobiographical fiction written collaboratively by Islamic woman author, Hanum Rais and her husband, Rangga Almahendra. Taking Faith and The City as the studied material, this study aims to discuss how Muslim men and women are stereotyped in the novel and how the story reflects the woman’s struggle in choosing between domestic responsibilities and aspiring career without losing her Islamic identity. The method of this study is close reading by identifying the representation of male and female character and reflection of woman struggle following the Islamic values.  Based on the findings, the researcher concluded that the character represents an Islamic woman who return to Islamic teachings and uphold the values taught by the Qur'an and Hadith. An educated Moslem woman tends to making adjustment for giving contribution to public spheres without leaving their faith and values.